Antimicrobial residue assessment in 5, 357 commercialized meat samples from the Spain-France cross-border area: A new approach for effective monitoring. (August 2022) - Serrano, M.J.; Elorduy, J.; Zabaleta, I.; Istamboulie, G.; González-Fandos, E.; Bousquet-Mélou, A.; Mata, L.; Aymard, C.; Martínez-Laorden, A.; Da Silva-Guedes, J.; Lacroix, M.; García-Gonzalo, D.; et al.
Abstract: Although antimicrobials are valuable allies in animal production, their extended use has led to unexpected threats associated with the emergence and propagation of antimicrobial resistance. Moreover, when withdrawal periods in food-producing animals are not observed, antimicrobial residues can access the food chain, causing direct toxicity, allergies, and/or intestinal microbiota dysbiosis in consumers. Given that Spain and France are the largest meat producers in the EU and also count among the top consumers of meat, our study's aim was to investigate the presence of antimicrobials in commercialized meat purchased in the Spain-France cross-border area (POCTEFA region). 5, 357 meat samples were collected from different animal species and a variety of different retailer types in Spain (Zaragoza, Bilbao, and Logroño) as well as in France (Toulouse and Perpignan). Meat samples were analysed by a screening method (Explorer®+QuinoScan®), yielding 194 positive samples, which were further evaluated by UPLC-QTOF (Ultra Performance Liquid Chromatography-Quadrupole Time of Flight) for confirmation. Chromatographic analyses found antimicrobial residues in 30 samples, although only 5 of them (0.093% of initial samples) were non-compliant according to the current legislation. Further studies suggested that this mismatch between screening and confirmatory analyses might be due to the presence of biologically active metabolites derived from degradation of antimicrobials that were not identified by the targeted UPLC-QTOF method, but which might play a decisive role in the inhibition of the biological Explorer® test. Although chromatographic techniques detect the marker compounds determined by European and national regulations, and although they are the methods selected for official control of antimicrobials in food, certain unknown metabolites might escape their monitoring. This thus suggests that biological tests are the most adequate ones in terms of ideal consumer health protection. Highlights: Antimicrobial residues were studied in 5, 357 commercialized meat samples. 3.5% of meat samples were detected as positive by a biological screening test. Only 0.093% of meat samples were non-compliant according to UPLC-QTOF. Biological tests present the advantage of detecting biologically active metabolites. Biological tests are the most adequate ones in terms of consumer health protection.